Isolation And Characterization Of Cadmium Resistant Bacteria From Industrial Wastewater - Abbas, Syed Zaghum (2014)
In the last few decades, cadmium removal by biological ways has received great attention. Nevertheless, for the growing of microorganisms that harbor many mechanisms for cadmium sequestration and may have great cadmium removal capacities, only small number of these studies employed in Malaysia. Sejak beberapa dekad yang lalu, penyingkiran Kadmium secara biologi telah mendapat perhatian yang besar. Walaupun banyak penemuan mengenai mekanisma penyingkiran Kadmium, hanya sebahagian kecil sahaja daripada kajian tersebut yang telah dilakukan di Malaysia.